Silagem de capim papuã (urochloa plantaginea) x silagem de sorgo (sorghum bicolor (l.) moench) na terminação de novilhos em confinamento - Argenta, Flânia Mônego (2012)
This work had as objective evaluate the use of Alexander grass silage as an alternative for substitution of sorghum silage in feedlot finishing steers. Twelve animals, with average weight and age initial of 245 kg and 20 months, respectively, pertaining to Nellore (N), Charolais (C), 21/32 N 11/32 C, 21/32 C 11/32 N, 43/64 N 21/64C e 43/64 C 21/64N genetic groups, were used. The diet was composed by roughage:concentrate relation of 50:50 (on dry matter basis), containing different sources of roughage: Alexander grass silage or sorghum silage, besides of concentrated compound by wheat bran, soybean meal, corn grain, limestone, sodium chloride and urea. The intakes of dry matter (DM), crude protein, ether extract, neutral detergent fiber and acid detergent fiber didn t differ between roughage sources, presenting average values of 10.18; 1.28; .20; 4.96 and 2.51 kg/day, respectively. However, ether extract intake per metabolic size and percentage of body weight were greater for animals that consumed sorghum silage, showing values of 2.74 and 2.36 g/metabolic size and .06 and .05 kg/100 kg of live weight. Similar behavior was observed for digestible energy intake, presenting values of 346.87 and 302.83 g/metabolic size and 8.10 and 7.02 kg/100 kg of live weight. Average daily weight gain, body condition and food conversion weren t influenced by roughage source, showing average values of 1.31 kg; 4.05 points and 7.78 kg of DM/weight gain, respectively. The use of different sources of roughage didn t affect the time spent with feeding, rumination and idle, presenting averages of 4.29; 11.52 and 8.06 h, respectively. The number of meals and time of daily meals (minutes) also weren t affect by treatments, showing values of 7.72 and 35.79. the number of chewed by ruminal bolus, time of chew per bolus, number of bolus, number of daily chew and total chewing time expressed in h/day didn t differ (P>.05) between treatments, presenting average values of 59; 53; 550.44; 32,059.5 and 12.36, respectively. The use of Alexander grass is a viable alternative to substitute sorghum silage without any variation on ingestive behavior and animal response.